2008
DOI: 10.1309/ajcpqy80hzwhhgzf
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sebia Capillarys Capillary Electrophoresis With the Primus High-Pressure Liquid Chromatography in the Evaluation of Hemoglobinopathies

Abstract: The Sebia Capillarys (capillary zone electrophoresis [CE]) and the Primus Resolution high-pressure liquid chromatography (HPLC) were used to prospectively evaluate 297 samples for hemoglobinopathies. Hemoglobin (Hb) A levels were similar on both techniques (mean, 96.2% and SD, 5.7% by CE; mean, 96.8% and SD, 5.5% by HPLC), but HbA2 levels were higher by CE (mean, 2.8%; SD, 0.8%) than by HPLC (mean, 2.3%; SD, 0.8%). HbS had higher values by CE (mean, 40.6%; SD, 18.9%) than by HPLC (mean, 38.4%; SD, 18.9%). In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 21 publications
3
65
0
3
Order By: Relevance
“…In this case, the quantification is not accurate. However, using CE, many variants can be detected easily and quantified accurately [6,7], including Hb New York, even if combined with Hb E, that can be also separated from Hb A [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the quantification is not accurate. However, using CE, many variants can be detected easily and quantified accurately [6,7], including Hb New York, even if combined with Hb E, that can be also separated from Hb A [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that CE was superior to HPLC for detection of thalassemia and Hb variants [6,7], however the performance of these methods for the detection of Hb New York was not explored. The aim of this study is to compare CE and HPLC for detection and quantification of Hb New York.…”
Section: Introductionmentioning
confidence: 99%
“…Minor and major HbBart's were also detected. This technique is also able to identify HbLepore (10). False positives found classically by IEF (2) are not seen with CE.…”
Section: Discussionmentioning
confidence: 86%
“…En cuanto a comparación técnica, cuando se empleó EC en el caso particular de la baja correlación de Hb A2 y aumento de los valores de la misma, se evidenció un resultado similar al obtenido por Keren y cols 21 , compararon EC y HPLC para el diagnóstico de hemoglobinopatías, obteniendo ligero aumento de Hb A2 por el primer método.…”
Section: Discussionunclassified